Motivation to enrol in a Master of Public Health postgraduate programme at a South African university - V Mathews; V Mathews (South African Medical Association, 2022)
Background. In the context of a curriculum embedded in social perspectives linked to validated Master of Public Health (MPH) competencies, blended learning is used for learning and teaching. However, in a changing technological environment and embarking on the Fourth Industrial Revolution, it becomes imperative to understand the target audience using blended learning as a postgraduate learning environment. Curriculum restructuring and redesign have to take into account changing patterns in the context, environment and target audience for postgraduate programmes in public health. Objectives. To determine the demographic profile of master's-level postgraduate public health students and their motivation for enrolling into a postgraduate programme. Methods. The study is a retrospective quantitative descriptive research design using secondary data from the application forms of all registered MPH postgraduate students enrolled for the degree from 2015 to 2019. Secondary data analysis was performed using descriptive analysis to calculate frequency, percentages, means and ranking order. Results. One hundred and eighty-four student records were analysed over the study period, with a 55% female and 45% male gender representation. South African students comprised 38% of the total number of students enrolled during the study period. The motivation to enrol in the MPH programme was to improve public health practice, specifically in the field of promotive and preventive aspects of public health. Further research into the motivation to enrol in a distance-learning postgraduate programme is required. Conclusion. The MPH programme attracts regional and international students from multidisciplinary fields, thereby improving public health practice by moving beyond clinical practice.